Answer:
3. 2x + y = −1
Step-by-step explanation:
To find the equation of the line, we write it first in the slope-intercept form:
![y=mx+q](https://tex.z-dn.net/?f=y%3Dmx%2Bq)
where
m is the slope
q is the y-intercept
From the graph, we see that the line crosses the y-axis at y = -1, so the y-intercept is -1:
![q=-1](https://tex.z-dn.net/?f=q%3D-1)
Now we have to find the slope, by calculating the rate of change of the line through 2 points:
![m=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Taking the two points at (-2,3) and (1,-3), we find:
![m=\frac{-3-3}{1-(-2)}=\frac{-6}{3}=-2](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-3-3%7D%7B1-%28-2%29%7D%3D%5Cfrac%7B-6%7D%7B3%7D%3D-2)
So the equation of the line is
![y=-2x-1](https://tex.z-dn.net/?f=y%3D-2x-1)
Now we have to re-arrange it in the standard form, so in the form
![ax+bx=c](https://tex.z-dn.net/?f=ax%2Bbx%3Dc)
where a, b and c are integer numbers.
To do that, we simply add +2x on both sides of the equation of the line in the slope-intercept form, and we get:
![y+2x=-1](https://tex.z-dn.net/?f=y%2B2x%3D-1)
So, option 3).